ANALYSIS OF THE INFLUENCE OF MUSLIM-FRIENDLY TOURISM IMPLEMENTATION ON THE DESTINATION IMAGE OF PETAK ENAM, WEST JAKARTA - Athallah Sukarno; Rendy Sarudin (LPPM Institut Pendidikan Nusantara Global, 2023)
This study analyzes the influence of Muslim-Friendly Tourism on the destination image of Petak Enam, West Jakarta. Using a quantitative method, data was collected from 100 visitors who have experienced the destination at least twice through questionnaires, observations, and various sources. The results show a significant influence of Muslim-Friendly Tourism on the destination image, supported by the t-test with a calculated t-value of 8.607 > the tabulated t-value of 1.660, and a significance level of 0.000. Multicollinearity and heteroskedasticity analyses confirm their absence. The coefficient of determination (R^2) is 0.431, indicating a 43.1% influence of variable X on variable Y, while the remaining 56.9% is influenced by other unexamined variables. The aim of this research is to enhance the tourism industry in Petak Enam by optimizing Muslim-Friendly Tourism and attracting Muslim travelers.